Effect of Electrophoretically Deposited Graphene Nanoplatelets on Flexural Properties of Carbon Fabric/Epoxy Laminated Composites - Ervina, Junaidi; Mariatti, Jaafar; Sinin, Hamdan; Hitoshi, Takagi (Penerbit Universiti Sains Malaysia, 2019)
In this study, the graphene nanoplatelets (GNP)/carbon fabric (CF)/epoxy (EP) hybrid laminated composites were fabricated via electrophoretic deposition (EPD) followed by hand lay-up assisted vacuum bagging technique. GNP were dispersed in two different colloidal suspensions, i.e., distilled water (DW) and N-dimethyformamide (DMF), and the effect of EPD GNP onto CF surface were investigated. The finding indicated that the electrophoretic mobility (EM) of GNP is slightly slower in DMF due to the higher viscosity of DMF (0.92 mPa.s) compared to DW (0.89 mPa.s). Zeta (ξ) potential of GNP were slightly higher in DMF, revealing the non-polar behaviour of GNP being easily dispersed in DMF due to its low polar and hydrogen-bonding strength. However, the higher current intensity was observed for the GNP-DW suspension, implying higher dielectric constant of DW adequate for effective deposition of GNP onto CF surface as confirmed via field-emission scanning electron microscopy (FESEM). The GNP-DMF/ CF/EP composites exhibit the highest flexural properties compared to GNP-DW/CF/EP composites. These findings proved the colloidal dispersibility of GNP in DW and DMF suspensions, respectively used in EPD govern the flexural properties of GNP/CF/EP hybrid laminated composites